Climate change impact on sandy beach erosion in Thailand - Hiripong Thepsiriamnuay (2020)
© 2019, Chiang Mai University. All rights reserved. This paper focuses on the spatial and temporal aspects of rising sea levels on sandy beach erosion in Thailand. The SimCLIM/CoastCLIM model with RCP 2.6 and RCP 8.5 was utilised to forecast changes in sea level and shoreline over the 1940 to 2100 period in Rayong, Nakhon Si Thammarat and Trang. Input parameters underlying the modified Brunn Rule were applied. Sand loss and forced people migration were estimated using fundamental equations. In the 1940 to 1995 period, estimated sea-level rise was 0.14 cm yr-1 and shoreline retreat was 5.33 m yr-1. Sea level is predicted to rise by 124.38 cm by 2100, compared to the 1995 level. Trang is the most vulnerable area with 507.90 m of eroded beaches and 2.15 km2 of sand loss. Rayong’s population is the most susceptible, with 873 people being forced to migrate. These results could be beneficial to national-scale data and adaptation planning processes in Thailand.